2003
DOI: 10.1175/1520-0493(2003)131<0206:imsetm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Idealized Model Simulations Examining the Mesoscale Structure of Winter Lake-Effect Circulations

Abstract: An array of 35 idealized mesoscale model simulations was used to examine environmental and surface forcing factors controlling the meso-␤-scale circulation structure resulting from cold flow over an isolated axisymmetric body of water at the midlatitudes. Wind speed, lake-air temperature difference, ambient atmospheric stability, and fetch distance were varied across previously observed ranges. Simulated meso-␤-scale lake-effect circulations occurred within three basic regimes (e.g., vortices, shoreline bands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 41 publications
5
77
1
Order By: Relevance
“…In both studied cases, the formation of snow bands agrees well with the results of Laird et al (2003a), who found that bands form when the ratio between the wind speed and fetch (V/L) is in the range of 0.02Á0.09 m s…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both studied cases, the formation of snow bands agrees well with the results of Laird et al (2003a), who found that bands form when the ratio between the wind speed and fetch (V/L) is in the range of 0.02Á0.09 m s…”
Section: Discussionmentioning
confidence: 99%
“…Type V are associated with a mesoscale vortex. Laird et al (2003aLaird et al ( , 2003b identified three common snow band morphologies in numerical investigations, which were associated with vortices, widespread coverage and shoreline bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than wind speed, the ratio of ambient wind speed U to fetch length L determines lake-effect morphology for an idealized circular lake (Laird et al, 2003a). When U/L is less than 0.02 m s −1 km −1 , mesoscale vortices form.…”
Section: How Does the Wind Speed Affect Band Formation?mentioning
confidence: 99%
“…Over the past 20 years, much progress has been made in simulating lake-effect circulations in the Great Lakes region with mesoscale models (Hjelmfelt, 1990;Laird et al, 2003aLaird et al, , 2003b. The processes generating lake-effect snow (Wiggin, 1950;Niziol, 1987;Niziol et al, 1995) have been studied in detail and short-term predictions have been significantly improved.…”
Section: Introductionmentioning
confidence: 99%